Use of an elasto-plastic model and strain measurements of embedded fibre Bragg grating sensors to detect Mode I delamination crack propagation in woven cloth (0/90) composite materials. (March 2018) - Kakei, Ayad Arab; Islam, Mainul; Leng, Jinsong; Epaarachchi, Jayantha A
Mode I fracture analysis being employed to study delamination damage in fibre-reinforced composite structures under in-plane and out-of-plane load applications. However, due to the significantly low yield strength of the matrix material and the infinitesimal thickness of the interface matrix layer, the actual delamination process can be assumed as a partially plastic process (elasto-plastic). A simple elasto-plastic model based on the strain field in the vicinity of the crack front was developed for Mode I crack propagation. In this study, a double cantilever beam experiment has been performed to study the proposed process using a 0/90-glass woven cloth sample. A fibre Bragg grating sensor has embedded closer to the delamination to measure the strain at the vicinity of the crack front. Strain energy release rate was calculated according to ASTM D5528. The model predictions were comparable with the calculated values according to ASTM D5528. Subsequently, a finite element analysis on Abaqus was performed using 'Cohesive Elements' to study the proposed elasto-plastic behaviour. The finite element analysis results have shown a very good correlation with double cantilever beam experimental results, and therefore, it can be concluded that Mode I delamination process of an fibre-reinforced polymer composite can be monitored successfully using an integral approach of fibre Bragg grating sensors measurements and the prediction of a newly proposed elasto-plastic model for Mode I delamination process.